Identifying factors causing decline in physical functionality of geriatric population. (June 2021) - Asim, Muhammad; Aftab, Muhammad; Bhatti, Sajjad Haider; Ahmad, Tanvir; Ali Shah, Syed Muhammad; Akram, Muhammad
The objective of the study was to find major correlates of decline in the physical functionality of the geriatric population. The main focus was the evaluation of demographic, social, economic, and health-related factors that have a potential impact on physical functionality. A sample of 423 elderly people were selected from district Faisalabad, Pakistan by using a snowball sampling approach. Statistical analysis was performed using frequency analysis and some tests for association like chi-square, Cramer's V, and gamma coefficient. It was observed that 42.8% of the respondents were independent in doing their all-routine work and the physical functional status decline was observed partially in 35.2% and completely in 22.0% of the respondents. Using frequency analysis and association measures, age, education, marital status, living with family, having an independent source of income, level of social network and support, having exercise routine were found to be significantly associated with functional status of elders. The study concluded that besides age and other demographic factors that cannot be controlled, the socio-economic factors can be improved to substantially reduce the decline in the physical functionality of the geriatric population.